Characterizing the interactions of edge dislocation dipole in hexagonal close packed Ti-Al alloys. (15th February 2019) - Wu, Hao; Leng, Jinfeng; Teng, Xinying; Su, Tao; Li, Qinggang; Li, Jinkai; Wu, Junyan; Xu, Daokui; Zhu, Yongchang
Abstract: The aim of the present work is to elucidate the interaction between dislocation dipoles decorated by trace addition of solute atoms in the model material of as-annealed coarse-grained Ti-3Al (weight percent, wt%) alloys. The morphology, activity, structure, strain field, and interaction of dislocation cores were systematically characterized. Theoretical predictions of equilibrium distribution of edge dislocation dipoles presenting an angle of 45° relative to each other were experimentally demonstrated. More importantly, we observed for the first time the 45°-rotating of strain fields around the dislocation core along a clockwise direction for stress equilibrium which is driven by the dislocation-dislocation interactions. Graphical abstract: Highlights: The interaction between edge dislocation dipoles was elucidated. Theoretical predictions of equilibrium distribution of edge dislocation dipoles were demonstrated. The 45°-rotating of strain fields around the dislocation core was observed for the first time.